1977
DOI: 10.1161/01.str.8.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Developmental course of hypertension and regional cerebral blood flow in stroke-prone spontaneously hypertensive rats.

Abstract: SUMMARY Regional cerebral blood flow (rCBF) was repeatedly measured by the hydrogen clearance method in the frontal cortex of stroke-prone spontaneously hypertensive rats (SHRSP) at the age of 50 days and thereafter. When SHRSP rats developed severe hypertension (over 200 mg Hg at the age of 60 days) rCBF began to decrease abruptly in the frontal cortex -one of the three predilection sites of stroke in these rats. In contrast, such a reduction in rCBF was not noted in either stroke-resistant spontaneously hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 33 publications
9
75
0
Order By: Relevance
“…In addition, others have shown a reduction in cerebral blood flow in conjunction with hypertension in SHR/SP with a marked decrease after 12 weeks, which is consistent with the timing we observed in hypoxic changes. [33][34][35] In conclusion, we used the SHR/SP with poor diet and carotid occlusion as a model for WM disease in VCI patients, and showed for the first time using direct pO 2 measurements with EPR a significant reduction in the O 2 in the deep WM. Our results suggest that changes in WM pO 2 may contribute to the selective injury in the deep WM unrelated to frank ischemic infarcts.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, others have shown a reduction in cerebral blood flow in conjunction with hypertension in SHR/SP with a marked decrease after 12 weeks, which is consistent with the timing we observed in hypoxic changes. [33][34][35] In conclusion, we used the SHR/SP with poor diet and carotid occlusion as a model for WM disease in VCI patients, and showed for the first time using direct pO 2 measurements with EPR a significant reduction in the O 2 in the deep WM. Our results suggest that changes in WM pO 2 may contribute to the selective injury in the deep WM unrelated to frank ischemic infarcts.…”
Section: Discussionmentioning
confidence: 84%
“…1,[11][12][13][14] In addition, studies showed that, as compared with normotensive subjects, hypertensive subjects have a blunted CBF response to neural tasks 11 and CO 2 stimulus. 15 In general, the brain maintains adequate CBF within a certain autoregulatory range independent of changes in systemic arterial pressure by adjusting vessel diameters of arteries and arterioles.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 It is known that the neuronal loss occurs with a reduction of gray matter volume in the CA1 subfield and dentate gyrus of the hippocampus in SHR at the age of 6 months or order, indicating that SHR can be a good animal model of vascular dementia. 8,9 SHRSP is also well known as an excellent model for subcortical vascular dementia accompanied by small-vessel pathology, because these rats show structural alterations of small cerebral arteries, 10 reduction in cerebral blood flow, 11 white matter lesions 12,13 and cognitive impairment. 14,15 We then examined differences in gene expression between microdissected hippocampal vessels with BBB impairment in SHRSP and those without the impairment in Wistar Kyoto (WKY) rats using a microarray assay and reported that the expression of osteopontin, a matricellular protein, was increased in BBB-damaged vessels in hypertensive SHRSP compared with that in vessels without BBB impairment in WKY rats.…”
Section: Introductionmentioning
confidence: 99%